Improved transmit beamforming design based on ADMM for low probability of intercept of FDA-MIMO radar - Pengcheng GONG; Yuntao WU (Tongxin xuebao)
Considering the low probability of intercept problem that the signal-dependent interference and the target were located in the same angle, an improved transmit beamforming design based on the alternating direction method of multipliers (ADMM) was proposed for multiple-input multiple-output with frequency diverse array radar.The transmit energy was minimized at the target under constraints of the energy at each transmitter and signal clutter-plus-noise ratio requirement.Subsequently, a cyclic algorithm was developed to tackle the non-convex design problem.Firstly, the optimal receive filter was obtained by generalized Rayleigh quotient.And then the transmit beamforming was optimized by employing auxiliary variables and ADMM to solve quadratic programming problem with fractional inequality constraint.Moreover, both the convergence and computational complexity of the proposed algorithm were discussed.Simulation results show that, compared with the semi-denite programming method, the proposed method not only attains the given antenna power, but also achieves the better mainlobe focusing performance at the target.Furthermore, the null levels at the clutter locations and the jamming directions obtained by the proposed method are -50 dB above.